The effect of an e-intervention on intellectual disability stigma among Nigerian and Kenyan internet users: a comparative randomised controlled trial - Odukoya, Deborah; Chege, Winfred; Scior, Katrina (Frontiers in Psychiatry, 2024)
The negative consequences of stigma for the wellbeing of people with disabilities have raised public and global health concerns. This study assessed the impact of an e-intervention to reduce intellectual disability (ID) stigma among Nigerian and Kenyan internet-users. Participants aged 18+ and citizens of Nigeria and Kenya were recruited through online advertising. Qualtrics, a web survey platform, randomly assigned (1:1) participants to watch either a short experimental or control film, while masked to their assignment. The experimental film featured education about ID and indirect contact. The control film was on an unrelated topic. Their attitudes were measured on three dimensions (affect, cognitions and behaviour) at three time points (baseline, post intervention and one-month follow-up). Between October 2016 and April 2017, 933 participants were randomised, 469 to the experimental condition and 464 to the control condition. Of these, 827 (89%) provided pre-and post-intervention data but only 287 (31%) were retained at followup. An intent-to-treat analysis revealed that participants in the experimental but not the control condition showed a positive shift in their attitudes towards people with ID over time. Their willingness to interact with people with ID increased post-intervention. A brief intervention that integrates education and indirect contact can make an effective contribution to efforts to reduce stigma faced by people with ID in Africa. Trial registered with the ISRCTN trial registry (number ISRCTN92574712).